Auditory brainstem responses: Stimulus variations - Gução, Ana Claudia Bianco [UNESP]; Romero, Ana Carla Leite [UNESP]; Lemes, Franciny Luque [UNESP]; Regaçone, Simone Fiuza [UNESP]; Valenti, Vitor Engracia [UNESP]; Frizzo, Ana Cláudia Figueiredo [UNESP] (Faculdade de Filosofia e Ciências, 2015)
Introduction: Auditory brainstem response is a response to external stimulation that represents the neural electrophysiological activity of the auditory system at the brainstem level. Variations due to the change in the presentation of stimuli help in the diagnosis of clinical conditions that affect the auditory nervous system. Objective: To characterize and compare the different polarity variations stimuli and presentation rates in adults with normal hearing. Methods: We investigated 20 students from a Center for Diagnosis and Rehabilitation, with no hearing impairment, all female aged 15-30 years old, who were screened for brainstem auditory evoked potential, which presented stimuli in different polarities ranges, including condensation and rarefaction in different presentation rates of 21.7, 27.7 and 47.7 stimuli per second. Results: We observed lower values of latencies of wave I in the three rates of stimulus presentation and wave V at the rate of 21.7/sec. rarefact when used, and also on the right ear and the same polarity , the gap interpeak I - III also had lower values for rates of introduction, as in the IR range the rate of 21.7/s. In overall comparison of groups in different polarities of stimulation, there was a significant difference only in rarefact. Conclusion: The understanding of the behavior of the electrophysiological response to variations of the stimulus is important and may serve as a reference for normal use of these measures in clinical practice.
Keywords: Auditory evoked potentials; Brain stem; Hearing; Normal values